1998
DOI: 10.1095/biolreprod59.4.918
|View full text |Cite
|
Sign up to set email alerts
|

Sperm and Oocyte Treatments to Improve the Formation of Male and Female Pronuclei and Subsequent Development Following Intracytoplasmic Sperm Injection into Bovine Oocytes1

Abstract: This study assessed pronuclear formation, the chromosomal constitution, and the developmental capacity of bovine zygotes formed by intracytoplasmic injection of oocytes with sperm, treated or not with dithiothreitol (DTT). Oocytes were matured in vitro for 22-24 h and then centrifuged so that sperm, prepared by swim-up in the presence or absence of 5 mM DTT, could be injected into the cleared area of the ooplasm. Injected oocytes were activated by treatment with 5 microM ionomycin (5 min) and, after a 3-h inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
145
3
4

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(163 citation statements)
references
References 50 publications
11
145
3
4
Order By: Relevance
“…The blastocyst yield in non-treated group (12%) is higher than those (0-8%) reported previously by several laboratories [8,10,11,[14][15][16], but comparable to or even lower than those (15-23%) in other reports [12,13]. However, blastocysts/ 235 cleavage rate in our study (30%) is comparable to that reported by Wei and Fukui [12] (32%) which indicates that a failure in the early post-fertilization events -from fertilization until cleavage-is the main determiner to the successful development after bovine ICSI.…”
Section: Discussioncontrasting
confidence: 66%
See 4 more Smart Citations
“…The blastocyst yield in non-treated group (12%) is higher than those (0-8%) reported previously by several laboratories [8,10,11,[14][15][16], but comparable to or even lower than those (15-23%) in other reports [12,13]. However, blastocysts/ 235 cleavage rate in our study (30%) is comparable to that reported by Wei and Fukui [12] (32%) which indicates that a failure in the early post-fertilization events -from fertilization until cleavage-is the main determiner to the successful development after bovine ICSI.…”
Section: Discussioncontrasting
confidence: 66%
“…This blastocyst yield is comparable to or even higher than those in many reports where bovine oocytes harvested from freshly collected ovaries were used for ICSI [8,10,11,[13][14][15][16]. Simultaneously with the ICSI experiments in the present study, high blastocyst yield (40 ± 3%, 90/223) was obtained after routine 225 IVF protocol, suggesting that oocytes harvested from stored ovaries carry sufficient in vitro developmental potential after IVF and ICSI if they were subjected to appropriate activation regimen.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations